Characterization and Quantification of Microplastics in Surface Water of Shitalakshya River, Bangladesh - Tohura, Umma; Islam, Md Mazharul; Shoeb, Mohammad (Dhaka University Journal of Science, 2025)
Microplastics (MPs) are a growing environmental concern due to their omni-presence and remarkable durability. The Shitalakshya river, located in the vicinity of industrial areas, faces a significant threat of MPs pollution, which may, in turn, disrupt the ecological balance and human health. In this study, surface water samples (W1-W10) were collected from the Shitalakshya river for the total counting of MPs with their morphological characterization by stereomicroscope. Chemical identification of MPs was carried out using ATR-FTIR technique and the obtained spectra were compared with the IR library. A total of 381 particles were counted and the abundance of MPs was 0.28 to 2.44 particles/L (average 1.524 particles/L). Examining shapes and colors, a maximum of 68.24% of MPs were fibers and 28.10% of black in color. Regarding particle size, MPs with 0-250 μm were most prevalent in surface water, constituting 56.43% of the total. The findings indicate that the predominant MPs were polyethylene (PE) and other MPs such as polystyrene (PS), polyvinylchloride (PVC), polypropylene (PP), etc. These results indicate that the Shitalakshya river is becoming contaminated by MPs and the pollution poses a risk to organisms in the urban river ecosystem, highlighting the need for immediate attention and corrective measures. Dhaka Univ. J. Sci. 73(1): 57-66, 2025 (January)